Qualitative data analysis: reflections, procedures, and some points for consideration - Dahal, Niroj (Frontiers in Research Metrics and Analytics, 2025)
This article adopts a constructivist grounded theory approach based on the principle of intersubjective relations and the co-construction of interpretations. Reflecting on the author's experiences as a tutor, supervisor, examiner, and reviewer to demystify qualitative data analysis (QDA), this article emphasizes member checking with participants to confirm the researchers' interpretations and collaboratively constructed meanings, addressing reflexivity, peer debriefing, and triangulation. QDA is framed as an iterative, dynamic process of extracting meaning from diverse data forms (field text, narrative, voice, reflective note, text, audio, and video). The procedures of data analysis and/or writing as a process of inquiry, such as data immersion, initial impressions, codes, categories, and theme developments, are explored across methods or methodologies, including autoethnography, participatory action research (PAR), narrative inquiry, grounded theory, phenomenology, ethnography, case study, and other alternative research methods or methodologies, with data saturation as the final stepping point when no new data and/or insights from field text, narrative, voice, reflective note, text, audio, or video are extracted. Challenges like generating an intersubjective construction of meaning with research participants and achieving data saturation are addressed through methods such as reflexivity, peer debriefing, member checking and triangulation. This article provides a practical guide for scholars on data analysis, incorporating reflections, procedures, and some points for consideration to ensure rigor and meaningful analysis.